Developmental air pollution exposure augments airway hyperreactivity, alters transcriptome, and DNA methylation in female adult progeny - Razia Zakarya; Yik Lung Chan; Baoming Wang; Andrew Thorpe; Single-Cell Mouse Lung Disease Atlas Consortium; Dikaia Xenaki; Kin Fai Ho; Hai Guo; Hui Chen; Brian G. Oliver; Christopher O’Neill (Communications Biology)
Abstract Maternal exposure to particulate air pollution increases the incidence and severity of asthma in offspring, yet the mechanisms for this are unclear. Known susceptibility loci are a minor component of this effect. We interrogate a mouse allergic airway disease model to assess epigenetic associations between maternal air pollution exposure and asthma responses in offspring. Maternal air pollution exposure increased allergic airway disease severity in adult offspring associated with a suppressed transcriptomic response. Control progeny showed differential expression of 2842 genes across several important pathways, whilst air pollutant progeny showed an 80% reduction in differentially expressed genes and abrogation of many pathway associations. Whole genome CpG methylome analysis following allergen challenge detected differential methylation regions across the genome. Differentially methylated regions were markedly reduced in air pollutant offspring, and this was most evident in intronic regions and some transposable element classes. This study shows that asthma in adult offspring of PM2.5 exposed mothers had a markedly repressed transcriptomic response, a proportion of which was associated with identifiable changes in the lung’s methylome. The results point to an epigenetic contribution to the severity of asthma in offspring of mothers exposed to particulate air pollution.